Laminated bamboo: alternative material of the future / Razak Wahab ... [et al.] - Wahab, Razak; W.Samsi, Hashim; Mustafa, Mohd. Tamizi; Hamid, Nurol Hisham (2002)
Gigantochloa scortechinii bamboo species were used to manufacture three-layers laminates and composite consisting of single-layer bamboo and two layers of wood veneers. Polyvinyl Acetate (PVAc) and Phenol Resorcinol Formaldehyde (PRF) were used as the binder for the process. Both, panels and a single strip were tested for its physical and mechanical properties in accordance of ASTM's and BS 373 with some modification. This paper will discuss on these properties of both panels and strips. Comparisons were also made to some common wood species. Results obtained were compared between glue types and laminates configuration.